Dendrimeric Guanidinoneomycin for Cellular Delivery of Bio‐macromolecules. (2nd December 2016) - Sganappa, Aurora; Wexselblatt, Ezequiel; Bellucci, Maria Cristina; Esko, Jeffrey D.; Tedeschi, Gabriella; Tor, Yitzhak; Volonterio, Alessandro
Abstract: We present the synthesis of polymeric amino‐ and guanidinoglycosides prepared by tethering neomycin and guanidinoneomycin to PAMAM dendrimers of generations 2 and 4. The ability of these conjugates to promote cellular uptake of high‐molecular‐weight cargo is discussed, together with their cytotoxicity and mechanisms of entry. We demonstrate that the presence of multiple guanidinoneomycin carriers on the PAMAM surface plays an important role in promoting cellular uptake of the dendrimers, maintaining the heparan sulfate specificity and negligible cytotoxicity typical of monomeric guanidinoglycoside molecular transporters. Abstract : Polymeric guanidinoglycoside vehicles : Comparing the cellular uptake of undecorated PAMAM dendrimers with that of PAMAM‐neomycin and ‐guanidinoneomycin conjugates shows that the presence of guanidinoneomycins, to a greater extent than that of neomycins, plays an important role in promoting cellular uptake of high‐molecular‐weight cargos.